SPATIAL VARIABILITY OF SOIL HYDRAULIC PROPERTIES IN JIBIA IRRIGATION PROJECT, KATSINA STATE, NIGERIA - Sani Sufiyanu; Sani Mahmud; Salihu Ahmad Pantami; Yakubu Muhammad Abdullahi; Garba Nuhu Harisu; Basiru Labaran Jazuli (Natural Resources and Sustainable Development, 2022)
Knowledge of the soil hydro-physical properties of any irrigation site is crucial in soil quality assessment and its management. This study was conducted to assess the aforementioned properties in the Jibia Irrigation Dam of Katsina, a Sudano-Sahelian region in Nigeria. After employing the grid soil sampling approach 144 samples were obtained and analyzed, the data obtained were subjected to descriptive statistics, correlation analysis and maps were created using the kriging technique. Findings were used to conclude the higher presence of sandy textured soils (loamy sand to sandy texture), Average Moisture content at Field Capacity (FC) of 0.332 %, Permanent Wilting Point (PWP) of 0.222 % and Available Water (AW) of 0.192 % were observed to be low with high Hydraulic conductivity making the soil require frequent irrigation. Semivariogram analysis showed that moisture content at FC and AW had weak spatial dependence (nugget-sill ratio > 75 %), moisture content at PWP had moderate spatial dependence (nugget-sill ratio, 25 – 75 %) while Saturated Hydraulic Conductivity (Ks) had strong spatial dependence (nugget-sill ratio <25 %). Linear, Gaussian, Exponential and models were used for hydraulic parameters based on nugget. Mean prediction error and root mean square values it was found the exponential model was the best fit for moisture content at FC, PWP and AW. While the quadratic model was the best fit for Ks. Sound management practices were recommended in terms of agricultural use of the soil in the study area.